A flame-retardant polymer electrolyte for high performance lithium metal batteries with an expanded operation temperature. Issue 6 (6th May 2021) - Xiang, Jingwei; Zhang, Yi; Zhang, Bao; Yuan, Lixia; Liu, Xueting; Cheng, Zexiao; Yang, Yan; Zhang, Xinxin; Li, Zhen; Shen, Yue; Jiang, Jianjun; Huang, Yunhui
Abstract : The well-designed flame-retardant polymer electrolyte greatly improves the safety and cycle life of high energy density lithium metal batteries. Abstract : Polymer electrolytes with high ionic conductivity, good interfacial stability and safety are in urgent demand for practical rechargeable lithium metal batteries (LMBs). Herein we propose a novel flame-retardant polymerized 1, 3-dioxolane electrolyte (PDE), which is in situ formed via a multifunctional tris(pentafluorophenyl)borane (TB) additive. The in situ formed PDE not only affords an integrated battery structure with stabilized electrode–electrolyte interface, but also achieves good flame retardancy, significantly expanded operating temperature limit and improved oxidative stability. Moreover, TB also contributes to a highly stable LiF-rich solid electrolyte interphase (SEI). In addition, the PDE has good compatibility with electrodes and polypropylene (PP) separator, hardly increasing the thickness of the battery, and the amount of additive TB is small, so there is no loss of gravimetric or volumetric energy density due to the polymerization. Based on the in situ formed PDE, Li–S batteries without the addition of LiNO3 demonstrate excellent cycle stability (>500 cycles) and a wide operating temperature (−20 to 50 °C); the high voltage Li–LiNi0.6 Co0.2 Mn0.2 O2 and Li–LiFePO4 batteries both exhibit excellent electrochemical performance (>1200 cycles). In addition, the ultrasonic imaging technique developed by our group also demonstrates no gas generation inside pouch cells using PDE. This work provides a facile and practical approach to design a highly stable polymer electrolyte for high performance LMBs.